Exclusion in community water governance in Bangladesh: An overlooked social issue - Sharma, Indu K.; Garrett, James; Joshi, Deepa (International Water Management Institute, 2023)
Bangladesh’s water management shifted toward a decentralized system in the 1990s, with more power to community, including the water management groups (WMGs). Empirical evidence, however, suggests unequal access to water among women and marginalized populations. To zoom into this, we reviewed studies published after 2000 to synthesize evidence on access to water among women and marginalized people, their recognition and representation in institutions, and barriers to those, in Bangladesh. The data extracted from 42 studies were coded in ATLAS Ti and analyzed thematically using social equity and feminist political ecology theories. The findings suggest a disconnect in the policy-practice landscape. Women, landless, and fishers were rarely included in the executive committees of WMGs despite their recognition in water management guidelines. Power dynamics significantly determined their representation and/or access to water. Technocratic policies, a lack of clear implementation strategy, a centralized water management system with a lack of local government involvement, fragmentation and lack of coordination across institutions, persistent socioeconomic barriers, and the capture of elite based on economic, political, and resource ownerships are key barriers resulting in exclusion in water management. Our review highlights recommendations to strengthen institutions and engage and empower communities. A clear policy implementation strategy incorporating power dynamics, enhancing the role of local institutions, a strong monitoring and evaluation system, community engagement and empowerment and setting boundary rules, a transformative approach to addressing broader social barriers to inequality are key recommendations to inclusive water governance.